Impact of zinc oxide nanoparticles on biosynthesis of thymoquinone in cell cultures of Nigella sativa - Ambreen; Mubarak Ali Khan; Afzal Raza; Reema Yousaf; Huma Ali; Hadeer Darwish (Plant Nano Biology)
The rising market interest for Nigella sativa (Black seeds) necessitates the development of cultivation strategies to enhance metabolites production. Zinc oxide nanoparticles (ZnO-NPs) have drawn global attention as efficient and bio safe elicitors for in vitro cultures, to enhance secondary metabolites production in medicinal plants. In this study, ZnO-NPs were utilized for establishment of callus and cell cultures in black seeds for the first time. Hypocotyl explants were cultured on Murashige and Skoog (MS) media with varying levels of ZnO-NPs, resulted in callus induction and biomass formation. Optimal response in callus growth parameters were observed when explants were grown on MS media supplemented with 60 mg/L ZnO-NPs, resulting in 71.2 % callus induction frequency, 28.2 g/L fresh biomass, 9.7 g/L dry biomass, and 63 % water content. A substantial increase in callus growth was observed when ZnO-NPs were combined with 6-Benzylaminopurine (BA) at ratio of 45:1.5 mg/L, resulting in 91.2 % callus induction frequency and 42.2 g/L fresh biomass. In cell suspension cultures, ZnO-NPs alone at 45 mg/L produced optimum callus biomass (60.9 g/L). However, in combination with BA, callus biomass did not increase significantly in cell cultures. Maximum accumulation of total phenolic content (TPC: 26.8 mg GAE/g DW; Gallic acid equivalent dry weight) and total flavonoid content (TFC: 19.5 mg QE/g DW; Quercetin equivalent dry weight) was observed in cell cultures treated with higher concentration (70 mg/L) of ZnO-NPs in the 5th week of the growth curve. Moreover, ZnO-NPs incremented substantially the Phenylalanine lyase (PAL), Superoxide dismutase (SOD) and Peroxidase (POD) enzyme activities in cell cultures. Nonetheless, Reverse Phase High Performance Liquid Chromatography (RP-HPLC) analysis indicated peak production of thymoquinone (168.5 mg/g FW) in cell cultures treated with 45 mg/L ZnO-NPs alone. This study offers a promising approach for commercial production of Nigella sativa biomass and bioactive metabolites.